Biliary drainage of the common bile duct with an enteral metal stent - Dek, Irene M (The WJG Press, 2009)
In this case report we present an elderly patient who was referred to our hospital with recurrent episodes of cholangitis that persisted after placement of five metal stents for a distal common bile duct (CBD) stenosis. All metal stents were endoscopically removed from the CBD by forceps after balloon dilatation of the papilla. A profoundly dilated CBD with sludge and concrements was seen. To ensure adequate bile drainage an enteral metal stent was inserted in the CBD. This case shows that proximally migrated uncovered metal stents in the CBD can be safely removed endoscopically under certain circumstances. We suggest that in the case of a CBD drainage problem due to an extremely dilated CBD, placement of an enteral metal stent in the CBD could be considered, especially in patients who are unfit for surgery.